Official tourist destination websites: Hierarchical analysis and assessment with ELECTRE-III-H. (July 2015) - Del Vasto-Terrientes, Luis; Fernández-Cavia, José; Huertas, Assumpció; Moreno, Antonio; Valls, Aida
Abstract: Official websites are important communication tools for tourist destinations. However, it is difficult to make a systematic and complete evaluation of their quality due to their diversity of functionalities, which makes them complex to analyse. This paper proposes the complementation of the WQI assessment system for Destination Marketing Organizations with the Multi-criteria Decision Aiding (MCDA) method ELECTRE. WQI assessment system contains several indicators (123) that can be organised in a hierarchical structure, which makes suitable the application of ELECTRE-III-H. ELECTRE-III-H method is able to reveal relevant preference relations among the websites with regard to different aspects (e.g., usability, architecture or persuasiveness), being a powerful tool to detect the strong and weak points of each website. The study is illustrated with the results of a pilot test that evaluates 10 touristic destination websites. Highlights: A combined methodology for analyzing tourist destination websites is presented. WQI assessment system is enhanced with ELECTRE-III-H method for decision support. The parameters to evaluate websites are organised in a hierarchical structure. Decisions to improve touristic brand marketing are illustrated with a pilot test.